1990
DOI: 10.1128/jb.172.5.2601-2607.1990
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic expression of Moraxella bovis fimbriae (pili) in Pseudomonas aeruginosa

Abstract: Type 4 fimbriae (pili) are found in a wide variety of gram-negative bacteria and are composed of small structural subunits which share significant sequence homology among different species, especially at their amino-terminal ends. Previous studies demonstrating morphogenetic expression of Bacteroides nodosus fimbriae from cloned subunit genes in Pseudomonas aeruginosa suggested that there is a common mechanism for type 4 fimbriae assembly and that the structural subunits are interchangeable (J. S. Mattick et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…It has been proposed that the infrastructural machinery for production and assembly of type 4 fimbriae is strongly conserved among the pathogens that produce this specific class of fimbriae. This is based on the evidence that the structural subunit from a variety of type 4 fimbriate bacteria can be produced and assembled in P. aeruginosa (3,12,19,27). For this reason, we investigated the possibility that a pilZ homolog exists in other species that produce type 4 fimbriae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the infrastructural machinery for production and assembly of type 4 fimbriae is strongly conserved among the pathogens that produce this specific class of fimbriae. This is based on the evidence that the structural subunit from a variety of type 4 fimbriate bacteria can be produced and assembled in P. aeruginosa (3,12,19,27). For this reason, we investigated the possibility that a pilZ homolog exists in other species that produce type 4 fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…This is indicated by the observation that P. aeruginosa is capable of producing fimbriae composed of heterologous subunits expressed from cloned subunit genes from D. nodosus, M. bovis, and N. gonorrhoeae (3,19,27). A number of homologs to the fimbria-associated genes of P. aeruginosa have been identified in other type 4 fimbriate bacteria (20,24).…”
mentioning
confidence: 99%
“…Bacteria bearing plasmids carrying cloned genes were grown on medium containing 150 g of carbenicillin per ml. Basic electron microscopy procedures were as described in the legend to on May 9, 2018 by guest http://jb.asm.org/ ginosa can form type IV pili from pilin subunits encoded by genes cloned from other species of bacteria (4,15,20,23,40), we tested whether PpdD could form pili in P. aeruginosa PAK A Ϫ lacking endogenous type IV pilin. Typical type IV pili were observed by electron microscopy in the control strains PAK and PAK A Ϫ A ϩ ( Fig.…”
Section: Figmentioning
confidence: 99%
“…These polypeptides, which range in molecular mass from 15 to about 18 kDa, contain a short, positively charged leader sequence of six or seven amino acids, an unusual modified amino acid at the amino terminus of the mature protein (usually N-methylphenylalanine), and a conserved and hydrophobic amino-terminal domain (13,38). Previous research has suggested that many components of the type IV fimbria biogenesis apparatus are likely to be functionally conserved across bacterial species (2,21,25,31). In some species, several of the genes involved in biogenesis of type IV fimbriae are clustered together close to the pilin structural gene.…”
mentioning
confidence: 99%